Job demands & job resources: predicting burnout and work engagement among teachers - Roslan, Nurul Aimi; Ho, Jo Ann; Ng, Siew Imm; Sambasivan, Murali (IACSIT Press, 2015)
In recent years, there has been a growing consensus among researchers and educators that studies related to teachers are pertinent to understand ways to improve teachers’ work engagement. This study adapted Hakanen, Schaufeli and Ahola [1] Job Demands-Resources Model to understand teachers’ burnout and work engagement in Malaysia. Questionnaires were sent out to 1,300 teachers in Negeri Sembilan schools and 600 responses were obtained after the one month data collection period. The data was analyzed through Structural Equation Modelling (SEM) using Amos 21.0. The research findings and implications are further discussed in this paper.